Comparative Analysis of the Flora of Morang District and Adjoining Areas of Nepal - Jha, S. (Our Nature, 2006)
Nine hundred and forty seven species of vascular plants under 661 genera and 172 families were recorded from Morang district and adjoining areas of Nepal. The genus-species ratio of the vascular plants in general and angiosperms in particular was 1:1.43 and 1:1.44, respectively; and 498 genera of vascular plants were represented by a single species only. On the basis of number of species, Polypodiaceae (11) was the largest family of pteridophytes, and Pinaceae (3) of gymnosperms. Among the angiosperms ten largest families were: Leguminosae (91)>Poaceae (80)> Asteraceae (57)>Euphorbiaceae (31)> Cyperaceae (28)> Rubiaceae(26) > Lamiaceae and Solanaceae (22 each) > Acanthaceae (21)> Orchidaceae (20) > Convolvulaceae (16). The biological spectrum of the study area was phanerotherophytic type. Key words: Conservation, Exotic weeds, Floristic analysis, Life forms, Reproductive seasons doi:10.3126/on.v3i1.336 Our Nature (2005) 3: 63-68